Rancang Bangun Sistem Informasi Puskesmas Berbasis Website Menggunakan Framework Laravel - Sopiah, Ripki Ramdani; Nasrulloh, Sofhian Fazrin (Indo-MathEdu Intellectuals Journal, 2025)
Primary Health Centers as the forefront of health services, face challenges in manual data management and suboptimal information dissemination. The issuance of Minister of Health Regulation No. 19 of 2024 mandates the digitization of services. This research aims to design and build a website-based Puskesmas information system to address these challenges. The research method used is Research and Development (R&D) with the Rapid Application Development (RAD) model, comprising Requirements Planning, Design Workshop, and Implementation phases. The result of this research is a functional information system with two main components: a public-facing frontend for information dissemination and a role-based admin panel (backend) for data management. The system successfully implements key features such as dynamic content management, an interactive activity schedule, a role-based multi-admin system, and a digital form for the Simple Elderly Health Screening (SKILAS). Based on the results of expert and user validation testing, the system achieved a functionality and usability feasibility score of 90%, categorized as "Highly Feasible". Therefore, the developed system is expected to be a solution to improve data management efficiency, accelerate reporting flows, and enhance the quality of health information services to the community.